Pengaruh Permainan Tradisional Balogo dan Benteng terhadap Kelincahan dan Daya Tahan Jantung Paru SD Negeri 1 Sababilah - yuriadi mepedeon; Rifky Riyandi Prastyawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to determine the effect of training using the Balogo and Benteng traditional games on the agility and cardiorespiratory endurance of students of SD Negeri 1 Sababilah (Sababilah 1 Elementary School). The background of this research is the need for effective and enjoyable learning in Physical Education for elementary school students, while simultaneously preserving local culture through traditional games. The research method used a quantitative approach with a pretest-posttest design and two treatment groups (Balogo and Benteng). The sample consisted of 24 extracurricular students, divided proportionally. Agility was measured by using a shuttle run test, while cardiorespiratory endurance was measured by using a 600-meter run test. The data analysis was performed by using paired sample t-tests and independent sample t-tests at a significance level of 0.05. The research findings reveal that training in the Balogo traditional game has a significant effect on agility (Sig. < 0.001; t = 48.738) and cardiorespiratory endurance (Sig. < 0.001; t = 10.981). Similarly, the traditional Benteng game significantly has impacted agility (Sig. < 0.001; t = 63.420) and cardiorespiratory endurance (Sig. < 0.001; t = 11.094). Furthermore, there is no any significant difference in the effects of Balogo and Benteng on agility (Sig. = 0.178) or cardiorespiratory endurance (Sig. = 0.460). These results conclude that both traditional games are equally effective in improving agility and cardiorespiratory endurance of elementary school students. Keywords: Balogo, Benteng, cardiorespiratory endurance, agility, traditional games